Bacterial diversity and co-occurrence patterns differ across a worldwide spatial distribution of habitats in glacier ecosystems - Zhang, Liyan; Delgado-Baquerizo, Manuel; Hotaling, Scott; Li, Yi; Xiangxin; Xu, Yifei; Chu, Haiyan (Functional Ecology, 2023)
Read the free Plain Language Summary for this article on the Journal blog. https://fesummaries.wordpress.com/2023/03/13/biodiversity-climatic-drivers-and-ecological-networks-of-glacier-microbiome-varied-across-habitats-at-a-global-scale/ Glaciers cover nearly 10% of the Earth's surface and are unique biomes dominated by microbial communities that support key ecosystem processes. The melting of glaciers is among the most conspicuous consequences of global climate change, with impacts on microbial ecology and associated biogeochemistry. However, we are still missing an integrative understanding of microbial biodiversity from divergent habitats associated with glaciers.Here, we compiled global microbiome metadata from 93 representative glaciers over 180 locations and used random forest, microbial ecological networks, and structural equation modeling to evaluate the biodiversity and environmental factors associated with the glacier microbiomes of seven contrasting habitats: water, epilithic biofilm, cryoconite, mat, ice, sediment and permafrost soil.The results showed that microbial diversity largely changed across habitats, with the highest in permafrost soil, followed by sediment, ice, mat, cryoconite, water, and epilithic biofilm. More importantly, we provided critical evidence that the environmental and climatic factors associated with the microbiomes of glaciers varied with glacier habitats. Microbial diversity in water was highly correlated with latitude, cryoconite microbial diversity was significantly (P = 0.01) correlated with pH, and permafrost soil and sediment microbial diversity were mainly explained by temperature (17.05% and 13.37%, respectively).Using ecological association network analysis, we identified some tightly linked common microbial taxa (e.g., Proteobacteria and Bacteroidetes) that were present in all the habitats and were vulnerable to climatic factors, such as temperature and precipitation. This study demonstrated that microbial diversity, drivers and co-occurrence patterns differ among ...